Mind the Gap: The Journey of Skull Base Specialties Toward Gender Parity - Patel, Shrey; Gall, Emily; Kosarchuk, Jacob; Toh, Elizabeth H.; Soneru, Christian; Noonan, Kathryn (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background There are increased efforts to promote gender diversity in skull base specialties.Aims/Objectives This study seeks to evaluate changes within neurotology, rhinology, and skull base neurosurgery (SBNS) over the past decade.Methods Information regarding fellows training in the past 10 years, current faculty members and fellowship directors, and grants and awards were extracted from the American Neurotology Society, American Rhinologic Society, and North American Skull Base Society Web sites, tabulated, and summarized. Chi-square analysis compared the proportional makeup of female fellows within related fields.Results In the past decade in neurotology, men constituted 89 of 128 (69.53%) fellows, 132 of 170 (77.64%) faculty members, and 25 of 29 (86.2%) fellowship directors. Within rhinology, men constituted 211 of 279 (75.63%) fellows, 113 of 141 (80.14%) faculty members, and 32 of 35 (91.4%) fellowship directors. In SBNS programs, men constituted 94 of 105 (90%) fellows, 120 of 133 (90%) faculty members, and 43 of 44 (97.73%) fellowship directors. In neurotology fellowships, the proportion of women increased (12%, p = 0.06) from 2012–2017 to 2018–2022. Similarly, SBNS and rhinology had statistically insignificant increases of 4.28% (p = 0.86) and 8.70% (p = 0.87).Conclusion The representation of women is consistent across all three skull base specialties. Although the overall number of women in each field is increasing, it changes slowly.Significance The gender makeup across all three skull base specialties is similar.
Keywords: skull base; neurosurgery; neurotology; gender